Effect Of Employee Capabilities And Commitments To The Performance Of The Tour And Travel Companies - Heriyanto, Heriyanto; Halilintar, Muhamad (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to: (1) analyze the positive and significant effect of the ability and work commitment of employees together on the performance of the company Tour & Travel (Travel Bureau), and (2) analyze the variables that have a dominant influence on the performance of the Tour & Travel Company (Travel Bureau). The analytical method used is Multiple Regression with the F-test and t-test. The results show that: (1). The first hypothesis which states that "the ability and commitment of employees to work together has a positive and significant effect on the performance of the Tour & Travel Company (Travel Bureau)" is accepted as true. This can be seen from the F test which shows the F-count > F-table, and the probability is less than 0.05, and (2). The second hypothesis which states "Among the two variables, the employee commitment variable has the greatest influence on the performance of the Tour & Travel company” is accepted. This can be seen from the highest double partial coefficient (r2) owned by the employee's work commitment variable of 28.0%.